2005
DOI: 10.1182/blood-2005-04-1632
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for CCR5 in the function of donor CD4+CD25+ regulatory T cells during acute graft-versus-host disease

Abstract: CD4 ؉ CD25 ؉ regulatory T cells (T regs ) have been shown to inhibit graft-versus-host disease (GVHD) in murine models, and this suppression was mediated by T regs expressing the lymphoid homing molecule L-selectin. Here, we demonstrate that T regs lacking expression of the chemokine receptor CCR5 were far less effective in preventing lethality from GVHD. Survival of irradiated recipient animals given transplants supplemented with CCR5 ؊/؊ T regs was significantly decreased, and GVHD scores were enhanced compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(204 citation statements)
references
References 70 publications
6
190
2
6
Order By: Relevance
“…Several studies have tried to solve this dilemma. It has been shown that CD4 + Treg from the donor or recipient can control GVHD after BM transplantation [21,[55][56][57][58]. In previous studies, we have found that donor DN-Treg could suppress donor CD8 + T cells, which caused GVHD in a single MHC-mismatched model [32].…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have tried to solve this dilemma. It has been shown that CD4 + Treg from the donor or recipient can control GVHD after BM transplantation [21,[55][56][57][58]. In previous studies, we have found that donor DN-Treg could suppress donor CD8 + T cells, which caused GVHD in a single MHC-mismatched model [32].…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, inflammation-seeking, effector/memory-like Treg are specialized to control ongoing immune responses directly within the inflammatory environment. Indeed, expression of trafficking receptors such as selectin ligands and chemokine receptors on effector/memorylike Treg subsets critically influences their in vivo suppressive capacity in inflammation [13,[15][16][17], suggesting that appropriate localization is indispensable for Treg function [2].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we and others have recently demonstrated that expression of certain HR such as selectin ligands and chemokine receptors on Treg subsets critically influences their suppressive capacity in vivo [43][44][45][46], suggesting that appropriate localization is indispensable for Treg function [30]. Although HR known from conventional T cells can also be found on Treg, it is presently unknown, if non-overlapping, organselective Treg subsets exist and how their trafficking is regulated.…”
Section: Introductionmentioning
confidence: 99%